Case report: Anal tuberculosis presenting as an anal fistula - Chaudhry, Muhammad Qasim; Abid, Shahab; Kayani, Naila (Frontiers in Gastroenterology, 2023)
This is a case of a young gentleman, who presented with complaints of hematochezia, weight loss and fluctuating fever for the past five months. The patient was a known case of Hirschsprung disease and Ulcerative colitis (IUC) and underwent a rectal Duhamel procedure in the past. On examination there was a fistula with an external opening at the anal verge. The clinical suspicion at this point was enterocutaneous fistula, abscess, and incontinence secondary to Hirschsprung disease. Investigations including MRI and sigmoidoscopy were carried out. A tissue from the anorectal junction was taken for histopathology review. Histopathological analysis suggested granulomatous inflammation with collection of epithelioid histiocytes along with caseating necrosis. This was consistent with the diagnosis of anal tuberculosis. The patient was started on a quadruple regimen of anti-tuberculous drugs (ATT). The patient six months into treatment has shown significant clinical improvement.